2019
DOI: 10.3390/jmse7060177
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Foredune Changes along the Southeast Australian Coastline: 1942–2014

Abstract: Foredunes are important features within coastal landscapes, yet there are relatively few medium to long-term studies on how they evolve and change over time. This study of Australia's New South Wales (NSW) foredunes has used 70 years of aerial photographs (or photogrammetry) and recent Light Detection and Ranging (LiDAR) datasets to assess multi-decadal fluctuations in foredune morphology. It was shown that over the past 70 years NSW foredunes have exhibited considerable spatial variation, ranging from accreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
1
8
0
1
Order By: Relevance
“…Sand supply from the lower shoreface to Perkins Beach is consistent with the long-term historical accretion of that shoreline (Doyle et al 2019b) and could represent a remnant process of shoreface lowering due to morphodynamic disequilibrium-stress, which would explain initial progradation of the Holocene Perkins-Windang barrier. That process has been shown to be the primary source of Holocene barrier progradation elsewhere in southeastern Australia (Kinsela et al 2016).…”
Section: Lower Shoreface and Active Zonesupporting
confidence: 58%
See 2 more Smart Citations
“…Sand supply from the lower shoreface to Perkins Beach is consistent with the long-term historical accretion of that shoreline (Doyle et al 2019b) and could represent a remnant process of shoreface lowering due to morphodynamic disequilibrium-stress, which would explain initial progradation of the Holocene Perkins-Windang barrier. That process has been shown to be the primary source of Holocene barrier progradation elsewhere in southeastern Australia (Kinsela et al 2016).…”
Section: Lower Shoreface and Active Zonesupporting
confidence: 58%
“…The result was similar, however, reflecting a previous study that identified the clockwise rotational trend (Cardno 2010). Doyle et al (2019b) found that Perkins-Windang Beach accreted by around 120 m 3 /m of shoreline on average during 1961-2014. The construction of the Lake Illawarra entrance training walls (2001)(2002)(2003)(2004)(2005)(2006)(2007) triggered scouring of sand shoals and channels within the tidal inlet, which appears to be driving progradation of the flood-tidal delta into the lake and aggradation of the ebb tidal delta outside the entrance, while increasing the tidal range within the lake (Young et al 2014;Wiecek et al 2016;Hart et al 2017).…”
Section: Historicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Arens et al, 2001;Jackson and Nordstrom, 2011;Bakker et al, 2012;Portz et al, 2015;Itzkin et al, 2020). Their impact on dune evolution on longer time-scales (decades to centuries) is less understood, as monitoring programs have been implemented too recently to cover these time scales (Bochev-van der Burgh et al, 2011;Doyle et al, 2019).…”
Section: Reshaping Impact and Lessonsmentioning
confidence: 99%
“…This holistic method illustrates the continuous evolution of around 250 m of the beach-dune system over the last 150 years including natural and anthropogenic evolutions (Figure 10c). This approach is complementary to information provided by the study of diachronic aerial (or satellite) photographs since the 1940s (Navaro-J o u r n a l P r e -p r o o f Journal Pre-proof Pons et al, 2016;Rader et al, 2018;Doyle et al, 2019;Jackson et al, 2019;Moulton et al, 2019) and makes it possible to extend the more recent 2DV database obtained using traditional topographic instruments and surveys (e.g. Bochev- Van der Burgh et al, 2011;Castelle et al, 2017b;Brodie et al, 2019;Nicolae Lerma et al, 2019).…”
Section: New Insight Of Paleo-topographic Profilingmentioning
confidence: 99%